Pressure Dependence of EXAFS Debye-Waller Factors in Crystals - Hung, Vu Van; Hieu, Ho Khac; Hung, Nguyen Van (Communications in Physics, 2012)
In present article the pressure dependence of Debye-Waller factors in crystals has been investigated by using statistical moment method and anharmonic correlated Einstein model. These two methods provide similar results which indicate that the Debye-Waller factors of crystals decreases slightly under high pressure. Our numerical results for several crystals are compared to other theoretical and experimental values and showed a good agreement.